A pilot randomised controlled trial comparing antipsychotic medication, to cognitive behavioural therapy to a combination of both in people with psychosis: rationale, study design and baseline data of the COMPARE trial. Issue 3 (3rd July 2017) - Law, Heather; Carter, Lucy; Sellers, Rachel; Emsley, Richard; Byrne, Rory; Davies, Linda; French, Paul; Haddad, Peter M.; Pitt, Elizabeth; Pyle, Melissa; Shiers, David; Yung, Alison R.; et al.
Abstract: Aims : Ongoing NICE guidance recommends research on the clinical and cost effectiveness of psychological treatment alone, compared to antipsychotic medication and compared to psychological treatment and antipsychotic medication combined. The COMPARE study (Cognitive behaviour therapy or Medication for Psychosis- A Randomised Evaluation) was a pilot trial designed to inform a definitive trial to answer this question. Method : COMPARE was a single-site pilot randomised controlled trial to compare a standardised Cognitive Behaviour Therapy (CBT) intervention to treatment with antipsychotic medication (APs) and a combined treatment (CBT plus APs) in adults with psychosis. Participants were assessed using the Positive and Negative Syndrome Scale (PANSS) and followed up at 6, 12, 24 and 52 weeks. The primary outcomes were recruitment and retention of participants. We surveyed a wider population of staff and service users to further inform feasibility of a definitive trial. Results: We report the characteristics of the recruited sample at baseline ( n = 75) and results from surveys. Conclusions: The study recruited to target demonstrating it is feasible to identify and recruit participants to a study of this kind. The survey results also suggest that such trials are feasible.Trial registration ISRCTN06022197.